2014
DOI: 10.1016/j.clinbiomech.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and kinetics of single-limb heel rise in diabetes related medial column foot deformity

Abstract: Background Diabetes-related medial column foot deformities contribute to high plantar pressure, joint instability, ulceration and amputation. Impaired foot function may be an early indicator of foot structural incompetence and contribute to deformity progression. This study examines the ability of single-limb heel rise multi-segmental kinematics and kinetics to identify midfoot and hindfoot dysfunction in those with diabetes-related medial column foot deformity. Methods Single-limb heel rise foot kinematics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The data for the heel rise task in this group of participants have been reported in detail in previous publications. 24 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data for the heel rise task in this group of participants have been reported in detail in previous publications. 24 …”
Section: Methodsmentioning
confidence: 99%
“…19-23 We have also identified that some individuals with DM have limited ability to plantarflex their forefoot on their hindfoot during the heel rise task, potentially compromising midfoot joint stability during loading. 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marker placement followed methods previously described. 27 Ankle dorsiflexion was calculated from the hindfoot on shank from the target lower extremity. Participants were positioned long sitting with knees extended and feet off the end of the plinth.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in DMPN multi-segment kinematics are also present during higher-level tasks. Hastings et al 56 . demonstrated decreased forefoot relative to rearfoot plantarflexion (lower medial longitudinal arch) during a heel raise task in people with DMPN and medial column deformity, in comparison to controls.…”
Section: Advancing Clinical Guidelinesmentioning
confidence: 99%